A Comprehensive Set of Juno In Situ and Remote Sensing Observations of the Ganymede Auroral Footprint. Issue 7 (5th April 2022) - Hue, V.; Szalay, J. R.; Greathouse, T. K.; Bonfond, B.; Kotsiaros, S.; Louis, C. K.; Sulaiman, A. H.; Clark, G.; Allegrini, F.; Gladstone, G. R.; Paranicas, C.; Versteeg, M. H.; et al.
Abstract: Jupiter's satellite auroral footprints are a manifestation of the satellite‐magnetosphere interaction of the Galilean moons. Juno's polar elliptical orbit enables crossing the magnetic flux tubes connecting each Galilean moon with their associated auroral emission. Its payload allows measuring the fields and particle population in the flux tubes while remotely sensing their associated auroral emissions. During its thirtieth perijove, Juno crossed the flux tube directly connected to Ganymede's leading footprint spot, a unique event in the entire Juno prime mission. Juno revealed a highly‐structured precipitating electron flux, up to 316 mW/m 2, while measuring both a small perturbation in the magnetic field azimuthal component and small Poynting flux with an estimated total downward current of 4.2 ± 1.2 kA. Based on the evolution of the footprint morphology and the field and particle measurements, Juno transited for the first time through a region connected to the transhemispheric electron beam of the Ganymede footprint. Plain Language Summary: The interaction between Jupiter's corotating plasma torus and the Galilean satellites generates a set of complex magnetospheric processes. One such interaction produces permanent auroral spots around Jupiter's northern and southern poles, known as footprints. For each close flyby, Juno's in situ instruments can measure such interaction. During its thirtieth perijove, Juno crossed the magnetic field lines connecting the interaction region of Ganymede with one of its auroral spots on Jupiter. This study describes and analyzes the set of measurements associated with that unique event. Key Points: Juno crossed the magnetic flux tube connected to Ganymede auroral footprint and recorded a multi‐instrument set of measurements Juno measured ∼316 mW/m 2 of precipitating electrons while magnetically tied to Ganymede's leading auroral footprint spot The associated Juno measurements suggest that it transited through a region linked to the transhemispheric electron beam